La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 601/2019 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2019)
Ejemplar completo: Revista de la ESG. Año 96, no. 601 (may-ago 2019). 59 p.